The Effectiveness of Communicative Approach in Enhancing Students’ Speech at SMA Negeri 1 Sukahaji Majalengka - Wiarsih, Asih (Foreign Language Instruction Probe, 2022)
The purpose of this research in general is to improve the quality of learning practices by using a communicative approach to teaching speech. The specific objectives to be achieved from the results of this study are 1). To obtain data on the ability of class X students of SMA Negeri 1 Sukahaji, Majalengka Regency in making speeches before learning by communicative approach. 2) To obtain data on the ability of Class X students of SMA Negeri 1 Sukahaji, Majalengka Regency in making speeches after learning by using a communicative approach. 3). To obtain data on the effectiveness of the use of a communicative approach in teaching speech to Class X students of SMA Negeri 1 Sukahaji, Majalengka Regency. The population in this study was class X SMA Negeri 1 Sukahaji Majalengka Regency with a total sample of 192. Data collection techniques were carried out through library research, pretest, and posttest. Students speaking ability before learning using a communicative approach is low. 61.0 % or more half of them do not yet have the ability to make speeches. The students speaking ability after learning by using a communicative approach there was increased the percentage reaching 72.6% or almost all of them had speeches. The use of an effective communicative approach can improve students’ abilities in teaching speech. The results of the calculation of the product-moment correlation test are known to have r = 0.884 or 88,4 % and based on the interpretation table, the correlation is very strong.